Model Pengukuran Tingkat Kepuasan Masyarakat Terhadap Penggunaan Jasa Transportasi Online di Wilayah Cirebon dengan Metode Fuzzy Servqual - Nursaka Putra; Ilwan Syafrinal; Marsani Asfi (Jurnal Sosial Humaniora, 2020)
Online transportation responds to people's needs in relation to publictransport. Online transportation, which in this context is Grab and Go-Jek, isan alternative that is favored by many people, especially in the Cirebon area.This study aims to measure the level of service satisfaction received and futurecustomer expectations of online transportation services. For our purpose, weuse Fuzzy Service Quality method which is used to determine the variablecustomer needs that are not met by calculating the GAP between the servicesprovided and the expectations of the customer as the Voice of Customer,where the data collection technique is carried out by distributingquestionnaires. The results are Reliability rank 2 with a value of 0.100,Responsiveness rank 4 with a value of 0.86, Assurance rank 3 with a value of0.090, Empathy rank 5 with a value of 0.040, Tangibles rank 1 with a value of0.139. Based on these results, we suggest that an empathy-related policymaking concerning professionalism should not become an obstacle.